Lower bounds for the warping degree of a knot projection - Atsushi Ohya; Ayaka Shimizu (My University, 2022)
The warping degree of an oriented knot diagram is the minimal number of crossings which we meet as an under-crossing first when we travel along the diagram from a fixed point. The warping degree of a knot projection is the minimal value of the warping degree for all oriented alternating diagrams obtained from the knot projection. In this paper, we consider the maximal number of regions which share no crossings for a knot projection with a fixed crossing, and give lower bounds for the warping degree.
Keywords: Image warping; Degree (music); Geometric and Algebraic Topology